Calidad de vida y malestar psicológico en pacientes que reciben tratamiento en la Unidad de Hemodiálisis del Hospital Isidro Ayora, periodo 2022 - Medina Encarnación, Jhoselyn Gabriela (2022)
Chronic kidney disease (CKD) and hemodialysis treatment entail several changes as well as physically and mentally, such as fatigue, stress, anxiety, depression, among others; on the other hand, the modification of their daily habits, such as receiving medical treatments, change of routines, and having to adapt to them, can be considered factors that can affect the quality of life of the individual and can be a possible trigger for psychological distress, becoming a public health problem. The main objective of this investigation work was to determine the relationship between quality of life and psychological distress in patients receiving treatment in the Hemodialysis Isidro Ayora Hospital, period 2022. The study had a quantitative approach, non-experimental, crosssectional and field, as well as descriptive and correlational, with the participation of 59 patients of the Hemodialysis Unit. For data collection, two psychological reagents were applied; the Quality of Life Questionnaire SF-36 and the List of Brief Symptoms (LSB-50), which reflected a regular level of quality of life and the absence of psychological distress, so it was concluded that there is no relationship between the variables established, however, because it is considered a population at risk, a preventive intervention plan focused on psychoeducation and prevention of psychological distress has been designed